2014
DOI: 10.1021/jf5014764
|View full text |Cite
|
Sign up to set email alerts
|

Leaching-Resistant Carrageenan-Based Colorimetric Oxygen Indicator Films for Intelligent Food Packaging

Abstract: Visual oxygen indicators can give information on the quality and safety of packaged food in an economic and simple manner by changing color based on the amount of oxygen in the packaging, which is related to food spoilage. In particular, ultraviolet (UV)-activated oxygen indicators have the advantages of in-pack activation and irreversibility; however, these dye-based oxygen indicator films suffer from dye leaching upon contact with water. In this work, we introduce carrageenans, which are natural sulfated pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The most widely known gas indicators are used to check oxygen and carbon dioxide concentrations. Due to the importance of these gases in food applications, much research has been devoted to the development of O 2 and CO 2 indicators over the last decade and in more recent years (Roberts, Lines, Reddy, & Hay, 2011;Jung, Puligundla, & Ko, 2012;Lee & Ko, 2014;Vu & Won, 2014). Most devices are based on redox dyes (e.g., methylene blue, 2,6-dichloroindophenol, or N,N,Nꞌ,Nꞌ-tetramethylp-phenylenediamine), a reducing compound (e.g., reducing sugars), and an alkaline compound (e.g., sodium hydroxide) (Kuswandi et al, 2011).…”
Section: Gas Indicatorsmentioning
confidence: 99%
“…The most widely known gas indicators are used to check oxygen and carbon dioxide concentrations. Due to the importance of these gases in food applications, much research has been devoted to the development of O 2 and CO 2 indicators over the last decade and in more recent years (Roberts, Lines, Reddy, & Hay, 2011;Jung, Puligundla, & Ko, 2012;Lee & Ko, 2014;Vu & Won, 2014). Most devices are based on redox dyes (e.g., methylene blue, 2,6-dichloroindophenol, or N,N,Nꞌ,Nꞌ-tetramethylp-phenylenediamine), a reducing compound (e.g., reducing sugars), and an alkaline compound (e.g., sodium hydroxide) (Kuswandi et al, 2011).…”
Section: Gas Indicatorsmentioning
confidence: 99%
“…For reference, this upward trend in the dye leakage continued beyond the 70 min around which we observed the hydrophilic polymer (HEC) starting to dissolve with the naked eye. It should be possible to suppress the dye leakage of the MB/GO-TiO 2 -based film in water to a greater degree by employing anionic polymers to interact with cationic MB as the encapsulating polymer [12,13].…”
Section: Mb Binding To Go-tio 2 Npsmentioning
confidence: 99%
“…When in contact with water contained in food, however, the oxygen indicator film suffers from the migration of redox dyes into food, which is prohibited under the regulation; it can lead to health problems [7,8]. Many attempts have been made to address such problems [9][10][11][12][13]; for example, the use of hydrophobic sulfonated polystyrene (SPS) as the encapsulating polymer made the film highly resistant to dye leaching, but the MB/TiO 2 /glycerol/SPS film showed very slow recovery of the color (5 days in ambient air) because of its hydrophobic property [9].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, for smart packaging design based on natural food colorants, some gases such as oxygen, carbon dioxide, hydrogen sulfide, ethylene, and volatile ammonia compounds have been applied. For instance, the UV-activated oxygen concentration indicator film is an improved and easy to use oxygen GI that was prepared using an encapsulating polymer with zein as a redox dye, thionine, and P25 TiO 2 , for the detection of oxygen and maintaining the dyes from leaching out in the packaging material and incorporation of biopolymeric hydroxyethyl cellulose with anthraquinone dye, Remazol brilliant blue R, and P25 TiO 2 for multifunctional anthraquinone-based sensors (UV, O 2 , and time) (Khankaew et al, 2017;Vu & Won, 2014). Also, Yanxiao et al (2015) reported a new room temperature gas sensor based on pigment-sensitized TiO 2 thin film (as the sensing layer) and natural pigments extracted from spinach, red radish, winter jasmine, and black rice.…”
Section: Gas-responsive Biodegradable Films Based On Natural Food Colmentioning
confidence: 99%